2020
DOI: 10.3390/cancers12061691
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Healthcare Cost of Adding Trastuzumab to Standard Chemotherapy for First-Line Treatment of Metastatic Gastric Cancer: A Population-Based Cohort Study

Abstract: A randomized clinical trial showed that trastuzumab, added to traditional chemotherapy, significantly improved overall survival in human epidermal growth factor receptor 2 (HER2)-overexpressing metastatic gastric cancer patients. This population-based study aimed at evaluating both the clinical and economic impact of trastuzumab in a real-world setting. By using the healthcare utilization databases of Lombardy, Italy, a cohort of patients newly diagnosed with metastatic gastric cancer during the period 2011–20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The median OS estimates described in this study are consistent with estimates reported by other real-world studies of patients with metastatic EGC in Canada, Germany, Italy and The Netherlands who received first-line trastuzumab therapy. In these studies, median OS ranged from 9.3 to 14.1 months [42][43][44][45]. In a study of 364 patients in Germany, median OS was 14.1 months in patients with HER2 status confirmed by IHC 3+ or IHC2+ confirmed by ISH and 9.1 months in patients with marginal HER2 status (defined as IHC2+ without confirmation by ISH) [42].…”
Section: Discussionmentioning
confidence: 99%
“…The median OS estimates described in this study are consistent with estimates reported by other real-world studies of patients with metastatic EGC in Canada, Germany, Italy and The Netherlands who received first-line trastuzumab therapy. In these studies, median OS ranged from 9.3 to 14.1 months [42][43][44][45]. In a study of 364 patients in Germany, median OS was 14.1 months in patients with HER2 status confirmed by IHC 3+ or IHC2+ confirmed by ISH and 9.1 months in patients with marginal HER2 status (defined as IHC2+ without confirmation by ISH) [42].…”
Section: Discussionmentioning
confidence: 99%
“…A cohort study using the Lombardy Health Care Database in Italy found that the mOS and restricted mean survival were 10.2 and 7.4 months, and 14.9 and 11.4 months, respectively, in the trastuzumab combined with chemotherapy group and standard chemotherapy group. [ 36 ] A large number of studies showed that trastuzumab combined with standard chemotherapy increased the mOS of patients with HER2-positive advanced GC. The latest Chinese Society of Clinical Oncology (CSCO) GC clinical guidelines, [ 2 ] the Japanese GC treatment guidelines, and the National Comprehensive Cancer Network (NCCN) GC clinical guidelines all recommend trastuzumab combined with fluorouracil or platinum for the first-line treatment of metastatic adenocarcinoma with high HER2 expression.…”
Section: Epidermal Growth Factor Receptor (Egfr) Family-targeted Drugsmentioning
confidence: 99%
“…At present, trastuzumab combined with chemotherapy has become the first-line treatment of choice for HER2-positive advanced GC. A cohort study using the Lombardy Health Care Database in Italy found that the mOS and restricted mean survival were 10.2 and 7.4 months, and 14.9 and 11.4 months, respectively, in the trastuzumab combined with chemotherapy group and standard chemotherapy group [36] . A large number of studies showed that trastuzumab combined with standard chemotherapy increased the mOS of patients with HER2-positive advanced GC.…”
Section: Epidermal Growth Factor Receptor (Egfr) Family-targeted Drugsmentioning
confidence: 99%
“…The development of HER-2 inhibitors has changed the landscape of treatment for patients suffering HER-2 positive tumors [8]. Adding HER-2-directed agents to the standard chemotherapeutic regimen has demonstrated survival benefits in several malignant tumors, including BC, gastric cancer, and gastroesophageal junction adenocarcinoma [9][10][11]. Trastuzumab is a prototype of humanized anti-HER-2 monoclonal therapeutic antibodies that selectively target the extracellular domain of the HER-2 receptor [12].…”
Section: Introductionmentioning
confidence: 99%